Last Word: Imagining the Future - Green, Ronald Michael (Kennedy Institute of Ethics journal, 2005)
, H. G. Wells warned, in 1895, not to allow economic injustices to become to so acute that they ultimately transform human biology. Wells's warning is all the more pertinent today as society contemplates the use of biotechnologies to manipulate or "enhance" the human genome.